2016
DOI: 10.14254/2071-789x.2016/9-1/15
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Gender on the Quality of University Patents and Public Research Centres in Andalusia: is it Better with a Female Presence?

Abstract: ABSTRACT. Much work has been done about the quality of patents as a tool to improve economic growth. However, investigations concerning the analysis of women's participation in technological research are very limited. The aim of this article is to determine if female participation in a specific invention influences the quality of the patent. The research is based on the analysis, of the information which shows 498 patent applications and 1838 inventors from Universities and Public Research Centres in Andalusia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…This research shows the influence of gender on innovation activity during the COVID-19 pandemic. In this regard, the results are in line with the theory that gender exerts an important influence on management style and business orientation towards innovation (Muñoz and Graña, 2016). In this context, Dezsö and Ross (2012) point out that female representation in senior management positions improves innovation.…”
Section: Discussionsupporting
confidence: 83%
“…This research shows the influence of gender on innovation activity during the COVID-19 pandemic. In this regard, the results are in line with the theory that gender exerts an important influence on management style and business orientation towards innovation (Muñoz and Graña, 2016). In this context, Dezsö and Ross (2012) point out that female representation in senior management positions improves innovation.…”
Section: Discussionsupporting
confidence: 83%
“…This study was innovative because instead of using a single indicator to assess patent quality (Fisch et al, 2016;Sterzi, 2013;Munoz and Grana, 2016), we used multiple indicators and did not subjectively assign them with fixed weights (OECD, 2013;Song and Li, 2014). Instead, a data-driven method was used to determine the weights of various patent indicators.…”
Section: Structural Model Of Patent Qualitymentioning
confidence: 99%
“…In this study, we conducted a literature review and summarized the factors that affect national patent quality through the use of a patent analysis. Previous studies have reported that the factors affecting patent quality include patent family size (Harhoff et al, 2003;Harhoff and Reitzig, 2002;Lanjouw and Schankerman, 2004), number of claims (Lanjouw and Schankerman, 2004;Sapsalis et al, 2006;Munoz and Grana, 2016), number of international patent classifications (IPCs) (Harhoff et al, 2003;Lerner, 1994), forward citations (Fisch et al, 2016;Hall et al, 2005;Popp et al, 2013;Sterzi, 2013), backward citations (Harhoff et al, 2003;Lanjouw and Schankerman, 2004), nonpatent references (NPRs) (Branstetter, 2005;Callaert et al, 2006) and maintenance time (Bessen, 2008;Schankerman and Pakes, 1986).…”
Section: Assessment Of Patent Qualitymentioning
confidence: 99%
“…While there is ample evidence that women patent less than men in comparable positions, a recent study from Spain (Muñoz and Graña (2016)) focusses on the effects of gender on the quality of patents. The main finding of this study is that the quality of the patent is higher when the inventor team includes both, male and female presence.…”
mentioning
confidence: 99%